2020
DOI: 10.1039/d0tc01220c
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state crystal growth of lead-free ferroelectrics

Abstract: Review article of the solid-state crystal growth (SSCG) technique and the progress of lead-free ferroelectric single crystals for piezoelectric applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 566 publications
0
31
0
Order By: Relevance
“…It is also particularly suited to grow crystals which melt incongruently or have volatile components, [ 12 ] while the disadvantage is that pores are entrapped during the pressing and sintering process and would cause potential problems in some applications, such as low transparency in optical materials and an increased hysteresis of the strain versus electric field in piezoelectric materials. [ 45 ]…”
Section: Single Crystal Fiber Fabrication Systemmentioning
confidence: 99%
“…It is also particularly suited to grow crystals which melt incongruently or have volatile components, [ 12 ] while the disadvantage is that pores are entrapped during the pressing and sintering process and would cause potential problems in some applications, such as low transparency in optical materials and an increased hysteresis of the strain versus electric field in piezoelectric materials. [ 45 ]…”
Section: Single Crystal Fiber Fabrication Systemmentioning
confidence: 99%
“…For the growth of single crystal, various conventional melt growth methods have been established, such as flux growth, top seeded solution growth, and Bridgman method, etc. 5 However, it is difficult to grow PZT single crystal using the above methods because the transition from liquid phase to a PZT solid solution exists the segregation of ZrO 2 . 6 Fortunately, solid-state crystal growth (SSCG) has emerged as a promising method for growth of complex, refractive component, incongruently melting systems with high volatility.…”
Section: Introductionmentioning
confidence: 99%
“…10 The orientation of the seed crystal has a strong impact on the single crystal growth behavior. 5 11 Seabaugh et al 12 reported extreme anisotropy of growth and growth behavior in the alumina system with rate controlling mechanism of diffusion through the liquid grain boundary phase and proposed that the concept of solubility of a specific crystal surface is dependent on crystal orientation. Messing et al 13 explained the crystal growth kinetics of PMN-PT grown on [001]c-, [110]c-, and [111]c-oriented BaTiO 3 seed crystals using the differences in localized solubility along various crystal planes relative to the matrix solubility, which was proposed by Seabaugh et al and Rheinheimer et al 14 However, the growth kinetics PZT single crystal with different orientation of seed crystal by SSCG has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The grains of KNN-based ceramics exhibit a faceted cube shape, signifying their very high interfacial energy anisotropy [ 28 , 29 , 30 ]. The faceted grain boundary makes normal grain growth difficult, owing to the absence of kink sites for the adsorption of atoms, which is associated with the low sinterability of KNN-based ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…The faceted grain boundary makes normal grain growth difficult, owing to the absence of kink sites for the adsorption of atoms, which is associated with the low sinterability of KNN-based ceramics. The grain growth of ceramics with faceted grain boundaries can be enabled by 2D nucleation and growth mechanisms [ 28 , 29 , 31 ]. The critical driving force (ΔG C ) for the formation of 2D nuclei on the grain surface is expressed as where ε is the step free energy of the 2D nucleus, Ω is the molar volume, k is Boltzmann’s constant, T is the temperature, and h is the height of the 2D nucleus.…”
Section: Introductionmentioning
confidence: 99%